From the Banned Telefilm to the Feature Film: the Two Versions of Alan Clarke’s Scum (1977-1979) - Nicole Cloarec (Revue LISA)
Alan Clarke’s Scum, originally made for the BBC’s Play for Today series in 1977, has become a cause célèbre in the history of film censorship. Although the film had already been scheduled, it was eventually banned and only broadcast in 1991, a year after the director’s death. How the decision was reached remains unclear but there is no denying that the film was deemed too controversial both by the Home Office and the newly-appointed BBC One controller Bill Cotton. Scum is set in a borstal, the name given to institutions for young offenders (a system that was to be abolished in 1982), and depicts life under a daily regimen of violence, bullying and racism. In response to the censoring of the original TV version, director Alan Clarke and screenwriter Roy Minton decided to re-shoot the film two years later for cinema release. Starting with a comparison between the two versions we will examine the different modalities of production and reception related to the two different media (television and cinema). Then we will analyse what makes the representation of a sensitive question such as living conditions in a borstal acceptable or not, considering the degrees of fictionalisation of the representation.